Awas Para Penyelundupan Barang (LEGAL DIALOGICA, 2025)
This research contains To find out and analyze the application of material and formal criminal law regarding the crime of storing important goods in certain quantities and at certain times when there is a shortage of goods and price fluctuations (verdict study). No: 14/Pid.Sus/2021/Pn.Mrs). To find out and analyze the Judge's Legal Considerations regarding the Crime of Storing Important Items in Quantities  ). To find out and analyze the Judge's Legal Considerations regarding the Crime of Storing Important Goods in Certain Quantities and Time When There is a Scarcity of Goods and Rising Prices (Study Decision No: 14/Pid.Sus/2021/Pn.Mrs) research results on the Application of material criminal law and the formality of this decision is appropriate. Materially, the defendant was proven to have violated Article 107 jo. Article 29 paragraph (1) Law no. 7 of 2014 regarding the storage of important goods during shortages and price fluctuations, with a prison sentence of 8 months as a deterrent effect. In formal criminal law, the period of detention that has been served is deducted from the sentence imposed, and the defendant remains in detention until the verdict is carried out. Evidence in the form of masks was handed over to the Covid-19 Task Force, while other items were destroyed or returned. Charging a case fee of IDR 2,000 is also in accordance with legal provisions, reflecting justice between the rights of the defendant and the interests of the community. In Decision no. 14/Pid.Sus/2021/PN MRS, the Panel of Judges chose the first alternative indictment based on Article 107 jo. Article 29 paragraph (1) Law no. 7 of 2014 related to the storage of masks by the defendant, Budi Prakoso Ramadhan, which caused a shortage of goods and price fluctuations. The judge rejected the defendant's defense regarding the status of the mask, considering it an important item, and sentenced him to 8 months in prison with a reduced prison term. The evidence is handed over for the benefit of the public, and the defendant is charged a court fee of IDR 2,000. This decision balances the deterrent effect and the public interest.Keywords: Storage prices fluctuate, shortage of goodsAbstrak:Penulisan ini bertujuan untuk : Untuk mengetahui dan menganalisis Penerapan Hukum Pidana Materil dan Formil tentang Tindak Pidana Menyimpanan Barang Penting Dalam Jumlah Dan Waktu Tertentu Pada Saat Terjadi Kelangkaan Barang Dan Gejolak Harga Naik (Studi Putusan No : 14/Pid.Sus/2021/Pn.Mrs). Untuk mengetahui dan menganalisis Pertimbangan Hukum Hakim terhadap Tindak Pidana Menyimpanan Barang Penting Dalam Jumlah Dan Waktu Tertentu Pada Saat Terjadi Kelangkaan Barang Dan Gejolak Harga Naik (Studi Putusan No : 14/Pid.Sus/2021/Pn.Mrs) hasil penelitian  Penerapan hukum pidana materiil dan formil dalam putusan ini sudah tepat. Secara materiil, terdakwa terbukti melanggar Pasal 107 jo. Pasal 29 ayat (1) UU No. 7 Tahun 2014 terkait penyimpanan barang penting saat kelangkaan dan gejolak harga, dengan pidana penjara 8 bulan sebagai efek jera. Dalam hukum pidana formil, masa penahanan yang telah dijalani dikurangkan dari pidana yang dijatuhkan, dan terdakwa tetap ditahan hingga putusan dijalankan. Barang bukti berupa masker diserahkan kepada Gugus Tugas Covid-19, sementara barang lainnya dimusnahkan atau dikembalikan. Pembebanan biaya perkara sebesar Rp 2.000 juga sesuai ketentuan hukum, mencerminkan keadilan antara hak terdakwa dan kepentingan masyarakat.Dalam Putusan No. 14/Pid.Sus/2021/PN MRS, Majelis Hakim memilih dakwaan alternatif pertama berdasarkan Pasal 107 jo. Pasal 29 ayat (1) UU No. 7 Tahun 2014 terkait penyimpanan masker oleh terdakwa, Budi Prakoso Ramadhan, yang menyebabkan kelangkaan barang dan gejolak harga. Hakim menolak pembelaan terdakwa mengenai status masker, menganggapnya sebagai barang penting, dan menjatuhkan pidana penjara 8 bulan dengan pengurangan masa tahanan. Barang bukti diserahkan untuk kepentingan masyarakat, dan terdakwa dibebankan biaya perkara sebesar Rp 2.000. Putusan ini menyeimbangkan efek jera dan kepentingan publik.Kata Kunci: Penyimpanan harga bergejolak naik,kelangkaan